Siri’ Na Pacce and The Reconstruction of Gender Roles: The Dynamics of Modern-Day Womanhood in Bugis-Makassar Society - Nur, Rezky Juniarsih; Komariah, Siti; Wilodati, Wilodati (Potret Pemikiran, 2024)
This research examines the dynamics of gender role reconstruction in Bugis-Makassar society in the context of the Siri’ na pacce tradition in the modern era. Using a qualitative approach with a descriptive-analytical method, this research applies in-depth interviews, participatory observation, and document analysis. The results show that Siri’ na pacce, a traditional concept that emphasizes shame and compassion, remains a significant influence on gender roles. However, these roles have been transformed by modernization and increased access to education. Women are increasingly participating in higher education and the public sphere, while men’s roles are evolving to include more domestic responsibilities. This reconstruction reflects the complex interaction between traditional values and modern influences. This study contributes to the understanding of how local cultural concepts adapt and shape gender identities amid global change, providing insights for culturally sensitive development policies.